2023
DOI: 10.1002/adts.202200856
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Eco‐Friendly Cs2SnI6 Based Tin Halide Perovskite Solar Cell through Device Modeling

Abstract: The choice of appropriate materials is of paramount importance in realizing a high efficiency perovskite solar cell. Lead free eco-friendly perovskite solar cell architecture is theoretically investigated using solar cell capacitance simulator (SCAPS) for device performance. Preliminary investigations on Cs 2 SnI 6 solar cell architectures have indicated that the presence of hole transport layer is crucial in achieving an open-circuit voltage greater than 0.6 V. The presence of a valence band offset between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 72 publications
(83 reference statements)
1
5
0
Order By: Relevance
“…This result aligns with previous research indicating that shallow imperfections have minimal impact on photocarrier recombination, resulting in a slight restriction to the V OC and J SC . 50 The findings given in this study also indicate that when the concentration of shallow N T exceeds 10 18 cm −3 , the efficiency of the PSC begins to decline significantly due to an intensified trapping–detrapping process. This finally results in a decrease in the mobility of photocarriers.…”
Section: Resultssupporting
confidence: 61%
“…This result aligns with previous research indicating that shallow imperfections have minimal impact on photocarrier recombination, resulting in a slight restriction to the V OC and J SC . 50 The findings given in this study also indicate that when the concentration of shallow N T exceeds 10 18 cm −3 , the efficiency of the PSC begins to decline significantly due to an intensified trapping–detrapping process. This finally results in a decrease in the mobility of photocarriers.…”
Section: Resultssupporting
confidence: 61%
“…Conversely, if the PVSK layer is excessively thick, it can lead to increased charge recombination, which will eventually result in a reduced short-circuit current density ( J SC ). , The open-circuit voltage ( V OC ) exhibits a slight decline as the PVSK layer thickness increases. It is important to note that V OC has a little dependency upon the thickness of the PVSK photoactive layer . On the other hand, J SC continues to increase until it reaches a saturation point at a quite high absorber thickness, about 600 nm.…”
Section: Resultsmentioning
confidence: 98%
“…It is important to note that V OC has a little dependency upon the thickness of the PVSK photoactive layer. 64 On the other hand, J SC continues to increase until it reaches a saturation point at a quite high absorber thickness, about 600 nm. A thicker PVSK layer provides more absorption of photons in PSCs as a result of the long diffusion length of photoinduced carriers.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for choosing relatively high values of the bulk defect density and interfacial defect density (1 × 10 15 and 1 × 10 14 cm −3 ) of the chalcogenide perovskite is because lower values are practically unrealisable. 10 Furthermore, in order to simulate a realistic cell, Au with a work function of 5.1 eV was chosen as the back contact before the quantum efficiency and J – V characteristics were calculated. It was found that after optimisation the J SC of the solar cell was nearly twice what it had practically achieved before optimisation of the aforementioned parameters.…”
Section: J–v Characteristics and Quantum Efficiencymentioning
confidence: 99%
“…While most of the theoretical investigations reported thus far have focused on the improvement in the efficiency of perovskite solar cells, 1–4 in practice, the presence of organic cation (CH 3 NH 3 + ) leads to long-term instability of the device upon exposure to heat, moisture, and UV radiation. In order to address these challenges, researchers have reported inorganic perovskite materials 5–11 and formamidinium-based perovskite materials 12,13 with efficiencies comparable to conventional organic–inorganic perovskite solar cells. Even though the optoelectronic properties of inorganic perovskites are promising, their performances have not surpassed that of hybrid perovskites due to their severe non-radiative recombination losses.…”
Section: Introductionmentioning
confidence: 99%